3.6k views
5 votes
6x^2-18x-18=6
CAN SOMEONE EXPLAIN PLS

2 Answers

0 votes
6(x^2-3x-3)=6
X^2-3x-3=1
X^2-3x-4=0
(X-4)(x+1)=0
X=4 x=-1
User Martin Gordon
by
5.5k points
5 votes
Simplifying
6x2 + -18x + -18 = 6

Reorder the terms:
-18 + -18x + 6x2 = 6

Solving
-18 + -18x + 6x2 = 6

Solving for variable 'x'.

Reorder the terms:
-18 + -6 + -18x + 6x2 = 6 + -6

Combine like terms: -18 + -6 = -24
-24 + -18x + 6x2 = 6 + -6

Combine like terms: 6 + -6 = 0
-24 + -18x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '6'.
6(-4 + -3x + x2) = 0

Factor a trinomial.
6((-1 + -1x)(4 + -1x)) = 0
User Eaten By A Grue
by
5.4k points